IMPACT OF BANK-SPECIFIC AND MACROECONOMIC DETERMINANTS ON FINANCIAL PERFORMANCE IN COMMERCIAL BANKS – CASE STUDY IN THAILAND AND VIETNAM - Keo, Vanney (PEOPLE: International Journal of Social Sciences, 2020)
Understanding the criteria affecting the profitability of commercial banks which are bank-specific and macroeconomic determinants is imperative for forming new strategies and capturing useful procedures to improve financial performance. The current study is to investigate the impact of bank characteristic and macroeconomic factors on financial performances and bank risks of commercial banks in Thailand and Vietnam. The empirical results reveal that non-performing loan ratio, bank capital ratio, total loan to total asset ratio, and GDP growth for medium banks have a significant impact on return on asset, return on equity, and LNZ-SCORE for the case of Thailand while bank capital ratio, total deposit to total asset ratio, GDP growth rate for small banks, and inflation show a significant relationship with return on asset, return on equity, and LNZ-SCORE for the case of Vietnam. Further studies should take other factors such as internal control, operation cost, and industrial factors into consideration for purpose of getting significant and accurate estimation results and also extend more related internal bank-specific variables.